Aquatic dicotyledons of North America : ecology, life history, and systematics - Les, Donald H. (Boca Raton, FL : Taylor & Francis, 2018)
"Aquatic Dicotyledons of North America: Ecology, Life History, and Systematics brings together a wealth of information on the natural history, ecology, and systematics of North American aquatic plants. Most books on aquatic plants have a taxonomic focus and are intended primarily for identification. Instead, this book provides a comprehensive overview of the biology of major aquatic species by compiling information from numerous sources that lie scattered among the primary literature, herbarium databases, and other reference materials. Included dicotyledon species are those having an obligate (OBL) wetland status, a designation used in the USACE National Wetland Plant List. Recent phylogenetic analyses are incorporated and rationale is provided for interpreting this information with respect to species relationships. This diverse assemblage of information will be useful to a wide range of interests including academic researchers, wildlife managers, students, and virtually anyone interested in the natural history of aquatic and wetland plants. Although focusing specifically on North America, the cosmopolitan distribution of many aquatic plants should make this an attractive text to people working virtually anywhere outside of the region as well. This book is an essential resource for assisting with wetland delineation. "--Provided by publisher.
part, Dicotyledons / Donald H. Les -- chapter 1 Dicotyledons I -- The ANA Grade and (3z(BMagnoliid(3y (BMonosulcates /s Donald H. Les -- chapter 2 Dicotyledons II -- Basal Tricolpates / Donald H. Les -- part, Eudicots (Tricolpate Dicots; Eudicotyledoneae) / Donald H. Les -- chapter 3 Core Eudicots: Dicotyledons III -- (3z(BCaryophyllid(3y (BTricolpates /s Donald H. Les -- chapter 4 Core Eudicots: Dicotyledons IV -- (3z(BRosid(3y (BTricolpates /s Donald H. Les -- chapter 5 Core Eudicots: Dicotyledons V -- (3z(BAsterid(3y (BTricolpates /s Donald H. Les.
Keywords: Aquatic plants -- North America; Dicotyledons -- North America